1978
DOI: 10.1126/science.25486
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Neurochemistry: Neuroregulators and Behavioral States

Abstract: There is compelling evidence that behavioral events after neurochemical function and that altered neurochemical function can change behavior. Such processes have been related both to neurotransmitters and to neuromodulators, together termed neuroregulators. Available research tools and theoretical constructs have begun to permit studies of certain types of behavior, primarily those related to emotional states and drives. This work is changing long-held concepts about severe mental disorders and the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

1978
1978
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(50 citation statements)
references
References 114 publications
0
47
0
3
Order By: Relevance
“…The list of peptides identified in both the central nervous system and the gastrointestinal tract is rapidly expanding (20)(21)(22)(23)(24)(25)(26)(27). Some of these gastrointestinal peptides, such as somatostatin, vasoactive intestinal polypeptide, and thyrotropin-releasing hormone, are included among the putative neuroregulators (28).…”
Section: Resultsmentioning
confidence: 99%
“…The list of peptides identified in both the central nervous system and the gastrointestinal tract is rapidly expanding (20)(21)(22)(23)(24)(25)(26)(27). Some of these gastrointestinal peptides, such as somatostatin, vasoactive intestinal polypeptide, and thyrotropin-releasing hormone, are included among the putative neuroregulators (28).…”
Section: Resultsmentioning
confidence: 99%
“…Neuroregulators are compounds that function either as neurotransmitters by acting on the transfer of information between a neuron and an adjacent target cell or as neuromodulators by amplifying or dampening neurotransmitter activity (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a correlation between this region and nociceptive or analgesia can be presumed. It was reported that the medial amygdala receives a 8-endorphinergic input from the basal hypothalamus (17), while the central nucleus contains a dense network of enke phalinergic interneurons (18). In addition, Rodgers (4) reported that the micro-injection of morphine into the medial amygdala produced a dose dependent increase in aversive thresholds.…”
Section: Discussionmentioning
confidence: 99%